Determination of Earnings Management: Reviewed from the Perspective of Audit Quality, Audit Committee, and Financial Performance - Tegar Apriansyah Wismajaya Putra; Moh Yudi Mahadianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
The purpose of this study is to evaluate earnings management factors in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) from 2023 to 2024 from the perspectives of audit quality, audit committee size, and financial performance. This study uses a quantitative approach based on secondary data obtained from the companies' annual reports. Using the modified Jones Model, discretionary ratios are used to calculate earnings management. Public accounting firm affiliation (Big Four and Non-Big Four) determines audit quality, audit committee size is measured by the number of members, and financial performance is proxied by Return on Assets (ROA). The results show that audit quality has a negative and significant impact on earnings management; therefore, high-quality auditors can suppress earnings management practices. There is no evidence that audit committees have a significant impact on earnings management, suggesting that their existence may be ineffective if not accompanied by optimal quality and oversight. Meanwhile, financial performance has a positive and significant impact on earnings management, indicating that companies with high profitability are more likely to engage in earnings adjustments. Simultaneously, audit quality, audit committee size, and financial performance have a significant influence on earnings management.